MOTIVASI MAHASISWI UNIVERSITAS RIAU MENJADI MODEL PHOTOGRAFI ( KAJIAN KASUS ) - Suprayitno, Eko; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Motivation is very important for life, Because with the motivation that one can pursue and achieve what is desired. Motivation is the reason underlying the background and someone that has passion and reason in making a clear objectives have been achieved and, thus, the person is capable of doing a job and his desire to believe and very strong. With the motivation of a person will be compelled to do something to be desired in order to achieve my goal. A person is said to have high motivation if the person has a very strong reason to achieve desired by the work done now. Similarly, when a person has a motivation in itself so that they look more perfect and more attractive look. This study focused on the student who became a model of photography at the University of Riau. And what the research is about the motivation and purpose of a mahasiwi want to be a model of photography, and how the process when he became a model of early photography and how to influence the impact of the model to study the course of a model. This research approach uses qualitative analysis that will explain the motivation, goals and factors a university mahasisiwi Riau become a model photography.Keyword = Motivation, Model, and Influence